Longitudinal frequency adaptations of surface EMG signals in female swimmers - Zech, A.; Edelmann-Nusser, J.; Witte, K.; Heller, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction The technique of surface EMG is often used to examine the co-ordination of muscles, the muscle fatigue and the relationship between force and neuromuscular activity. Several studies of myoelectric signals in swimming have been published (e. g. Ikai et al., 1964; Kipke, 1966; Clarys, 1988). However, there are no time-frequency-analyses of surface EMGs in swimming. In recent time, the time-variant spectral analysis has been established as a valid method to analyse non-stationary biological signals (Witte et al. 2000, 2003). The aim of this longitudinal study was to investigate changes in the time-variant frequencies of surface EMG signals during adaptation in highly skilled swimmers. Methods We analysed swim specific movements of nine female swimmers on an isokinetic swim bench over a training period of nine months in 2002/2003. Surface EMG-signals of the m. tricepes brachii (caput laterale and caput longum) and m. latissimus dorsi and mechanical power were acquired over a 120-second period of a maximal voluntary endurance-load-swim-bench-exercise. Time-dependent spectra and median frequency were analysed using the method of time-variant spectral analysis (Schack et al., 1995). Results The time-dependent spectra: at the end of the exercise the higher wave bands vanished. The median frequencies decreased during the exercise for all swimmers as shown in Figure 1. These effects are typical for progressive fatigue. The longitudinal analyses were done in separate case-reports for each swimmer because of the different levels of the swimmers: The top elite swimmer (world champion) showed the following changes: After the first phase of high load training the mean mechanical power increased distinctly and persist on this level over the remaining time of the training season. At the beginning of each taper-period after a high load training phase the mean median frequency showed higher values than before (Figure 2). I. e., after the first phase of high load training the mechanical power persisted almost constant at the same level while the mean median frequency varied with the training-season according to the amplitude and the intensy of the training. These training-dependent frequency changes were observed in the other swimmers, too. Discussion/Conclusion The results suggest that the mean median frequency is not a factor of physical performance but rather of its gradient (before phase of overreaching: phase of physical degeneration with low mean frequencies and negative gradient of the performance and after high load training phase: phase of supercompensation with high mean frequencies and positive gradient of the performance).